Simultaneous Determination of Indium and Aluminum by Adsorptive Stripping Voltammetry in Presence of Eriochrome Blue Black R - Li, Jun-Hua; Kuang, Dai-Zhi; Feng, Yong-Lan; Liu, Meng-Qin (Asian Journal of Chemistry, 2011)
A sensitive and selective method for the simultaneous determination of trace amounts of indium and aluminum by adsorptive stripping voltammetry was developed using Eriochrome blue black R [1-(2-hydroxy-1-naphthylazo)-2-naphthol-4-sulfonic acid sodium salt, EBBR] as selective complexing agent on the multi-walled carbon nanotubes (MWCNTs) modified electrode. In a single scan, both metals gave peaks that were distinctly separated by 0.67 V allowing their determination in the presence of each other. Optimal analytical conditions were found to be: Eriochrome blue black R concentration of 40 μM, pH of 6.0 and adsorptive potential of -1.0 V versus saturated calomel electrode (SCE). With an accumulation time of 30 s, the peak currents are proportional to the concentration of indium in the range of 5.0 × 10-9 to 1.0 × 10-6 M and to that of aluminum in the range of 1.0 × 10-8 to 8.0 × 10-7 M. The detection limits (S/N = 3) are 1.0 × 10-9 and 8.0 × 10-9 M, respectively. This procedure was applied to simultaneous determination of indium and aluminum in some real samples with satisfactory results.